Conceptual Analysis of Business Unit’s Strategic Position of Russian Diversified Company (within Marakon Associates Profitability Matrix) - КочугуеваМаргарита Николаевна; МошкареваД. A.; ШадринаН. М.; ЮловаС. М. (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2012)
Author: Margarita N. Kochugueva - National Research University "Higher School of Economics." The main purpose of the present study is the analysis of strategic position of business divisions and business units within Marakon Associates profitability matrix. This matrix allows investigate the position of every business unit (or division) with regards to three key parameters: profitability, growth and capability of cash generation. For the study data of the large Russian holding «Mezhregionalnykh Raspredelitelnykh Setevykh Kompaniy (MRSK)» was used. We briefly examined the methodology of application Marakon Associates matrix, provided an overview of the company and industry, and performed a portfolio analysis of business units (divisions) position that belong to the holding in 2009 and 2010.